2018
DOI: 10.5897/ijnam2018.0243
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with nutritional status among lactating mothers at Shashemene Woreda, West Arsi Zone, Oromia, Ethiopia: A comparative cross-sectional study

Abstract: Inadequate nutritional intake prior to pregnancy, during pregnancy and lactation process increases postnatal nutritional stresses and health risk of the mother resulting in a high maternal mortality. The aim of this study was to compare nutritional status and associated factors of urban and rural lactating women from Shashemene Woreda, West Arsi Zone of Oromia, Ethiopia. A community based comparative cross-sectional study was conducted among 484 randomly selected lactating mothers from six kebeles. Anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 7 publications
0
19
1
Order By: Relevance
“…Regarding the meal frequency of pregnant and lactating women in Ethiopia, it was reported by 23 studies (Abriha et al, 2014;Alemayehu & Tesema, 2015;Aliwo et al, 2019;Boke & Geremew, 2018;Kobiro et al, 2020;Demilew et al, 2020;Desalegn et al, 2018;Desta et al, 2019;Diddana, 2019;Duko et al, 2018;Engidaw et al, 2019;Eramo, 2018;Gizahewu et al, 2019;Haileslassie et al, 2013;Hailu & Woldemichael, 2019;Jemal & Awol, 2019;Kumera et al, 2015;Nigatu et al, 2018;Sitotaw et al, 2017;Sonko, 2016;Tikuye et al, 2019;Weldehaweria et al, 2016) with a total of 9,447 study subjects. Of the total study subjects, 7,554 (80%) of pregnant and lactating women ate ≤3 times per day, whereas 1854 (20%) of them ate ≥4 times per day (Table 1).…”
Section: Dietary Practice and Meal Frequencies Of Pregnant And Lactating Women In Ethiopiamentioning
confidence: 99%
“…Regarding the meal frequency of pregnant and lactating women in Ethiopia, it was reported by 23 studies (Abriha et al, 2014;Alemayehu & Tesema, 2015;Aliwo et al, 2019;Boke & Geremew, 2018;Kobiro et al, 2020;Demilew et al, 2020;Desalegn et al, 2018;Desta et al, 2019;Diddana, 2019;Duko et al, 2018;Engidaw et al, 2019;Eramo, 2018;Gizahewu et al, 2019;Haileslassie et al, 2013;Hailu & Woldemichael, 2019;Jemal & Awol, 2019;Kumera et al, 2015;Nigatu et al, 2018;Sitotaw et al, 2017;Sonko, 2016;Tikuye et al, 2019;Weldehaweria et al, 2016) with a total of 9,447 study subjects. Of the total study subjects, 7,554 (80%) of pregnant and lactating women ate ≤3 times per day, whereas 1854 (20%) of them ate ≥4 times per day (Table 1).…”
Section: Dietary Practice and Meal Frequencies Of Pregnant And Lactating Women In Ethiopiamentioning
confidence: 99%
“…The consequences of poor nutrition to both baby and mother are not recognized by women and indicate the degree of women's awareness about diet, which is not adequate [ 8 ]. Understanding regarding the need for improved nutritional intake of lactating women was reported by most participants in West Arsi Zone, Oromia, Ethiopia [ 45 ]. It is an imperative drift as women's nutrition during the pregnancy period is significant to reduce complications related to pregnancy such as morbidity/morbidity to mothers and infants.…”
Section: Basic Concept Of Nutritional Practicesmentioning
confidence: 99%
“…It also reported that most women in Ethiopia did not follow a healthy eating style and knew major food groups during the pregnancy period. About 71.2%, 68.6%, and 39.3% of lactating women were not eating meals additionally [ 37 , 45 , 47 ], respectively. This dietary behavior of pregnant and lactating women was also common and further supported by the formative finding of [ 48 ].…”
Section: Basic Concept Of Nutritional Practicesmentioning
confidence: 99%
See 2 more Smart Citations